2010
DOI: 10.1007/s10936-010-9148-9
|View full text |Cite
|
Sign up to set email alerts
|

The Real-Time Processing of Sluiced Sentences

Abstract: Ellipsis refers to an element that is absent from the input but whose meaning can nonetheless be recovered from context. In this cross-modal priming study, we examined the online processing of Sluicing, an ellipsis whose antecedent is an entire clause: The handyman threw a book to the programmer but I don’t know which book the handyman threw to the programmerellipsis. To understand such an elliptical construction, the listener arguably must ‘fill in’ the missing material (“the handyman threw___ to the programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
0
17
1
Order By: Relevance
“…Experimental evidence has repeatedly demonstrated that an elliptical clause is processed more quickly following a parallel antecedent (Arregui, Clifton, Frazier, & Moulton, 2006; Dickey & Bunger, 2011; Mauner, Tanenhaus, & Carlson, 1995; Tanenhaus & Carlson, 1990). Furthermore, an antecedent seems to be re-activated earlier in elliptical constructions conjoined by a parallelism-implying conjunction (“and”) than in elliptical sentences otherwise conjoined (Poirier, Wolfinger, Spellman, & Shapiro, 2010; Shapiro & Hestvik, 1995). …”
Section: The Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evidence has repeatedly demonstrated that an elliptical clause is processed more quickly following a parallel antecedent (Arregui, Clifton, Frazier, & Moulton, 2006; Dickey & Bunger, 2011; Mauner, Tanenhaus, & Carlson, 1995; Tanenhaus & Carlson, 1990). Furthermore, an antecedent seems to be re-activated earlier in elliptical constructions conjoined by a parallelism-implying conjunction (“and”) than in elliptical sentences otherwise conjoined (Poirier, Wolfinger, Spellman, & Shapiro, 2010; Shapiro & Hestvik, 1995). …”
Section: The Current Studymentioning
confidence: 99%
“…Intriguingly, ellipsis in these constructions is posited even before its existence can be unequivocally inferred from the input. In contrast, it is delayed in constructions conjoined by conjunctions that are not associated with parallelism (Poirier et al, 2010; Shapiro & Hestvik, 1995, Exp. 2).…”
Section: Experiments 2: Antecedent Reactivation At the Elision Sitementioning
confidence: 99%
“…–have very different properties, there is widespread evidence that they are biased to associate with the most local constituent, possibly due to default focus placement on the most embedded constituent (Carlson et al, 2009). In the case of sluicing in (14a), there is a bias to associate the wh -element who with the object correlate, someone , which is the nearest possible candidate, instead of the subject somebody (Frazier & Clifton, 1998; Poirier, Wolfinger, Spellman, & Shapiro, 2010). Although this bias can be partly counteracted by focal stress on non-local correlates (Carlson et al, 2009), as well as other indicators of discourse prominence, there is a processing cost associated with retrieving a structurally dispreferred correlate (Carlson, 2001, 2002, 2013; Stolterfoht et al, 2007; Harris, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Though the issue as to the reconstruction mechanism is not yet settled, findings from studies on verb-phrase ellipsis and on sluicing, i.e. elision of an entire clause except for a wh-word (e.g., Humphrey ordered something but Spencer doesn't know what Humphrey ordered) converge in suggesting that the elided element is reconstructed in real time -immediately when or shortly after encountering the ellipsis (e.g., Callahan, Walenski, & Love, 2012;Poirier, Wolfinger, Spellman, & Shapiro, 2010;Shapiro & Hestvik, 1995;Shapiro, Hestvik, Lesan, & Garcis, 2003: Yoshida, Dickey, & Sturt, 2013.…”
Section: Introductionmentioning
confidence: 99%